Geography and island geomorphology shape fish assemblage structure on isolated coral reef systems - Bennett, Scott; Halford, A.; Choat, J.; Hobbs, Jean-Paul; Santana Garcon, Julia; Ayling, A.; Harvey, Euan; Newman, Stephen (John Wiley & Sons, 2018)
We quantify the relative importance of multi-scale drivers of reef fish assemblage structure on isolated coral reefs at the intersection of the Indian and Indo-Pacific biogeographical provinces. Large (>30 cm), functionally-important and commonly targeted species of fish, were surveyed on the outer reef crest/front at 38 coral reef sites spread across three oceanic coral reef systems (i.e. Christmas Island, Cocos (Keeling) Islands and the Rowley Shoals), in the tropical Indian Ocean (c. 1.126 x 106 km2). The effects of coral cover, exposure, fishing pressure, lagoon size and geographical context, on observed patterns of fish assemblage structure were modelled using Multivariate Regression Trees. Reef fish assemblages were clearly separated in space with geographical location explaining ~53 % of the observed variation. Lagoon size, within each isolated reef system was an equally effective proxy for explaining fish assemblage structure. Among local-scale variables, ‘distance from port’, a proxy for the influence of fishing, explained 5.2% of total variation and separated the four most isolated reefs from Cocos (Keeling) Island, from reefs with closer boating access. Other factors were not significant. Major divisions in assemblage structure were driven by sister taxa that displayed little geographical overlap between reef systems and low abundances of several species on Christmas Island corresponding to small lagoon habitats. Exclusion of geographical context from the analysis resulted in local processes explaining 47.3% of the variation, highlighting the importance of controlling for spatial correlation to understand the drivers of fish assemblage structure. Our results suggest reef fish assemblage structure on remote coral reef systems in the tropical eastern Indian Ocean reflects a biogeographical legacy of isolation between Indian and Pacific fish faunas and geomorphological variation within the region, more than local fishing pressure or reef condition. Our findings re-emphasise the importance that historical processes play in structuring contemporary biotic communities.